1994
DOI: 10.1111/j.2044-8279.1994.tb01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived locus of causality, goal orientations, and perceived competence in school physical education classes

Abstract: Ryan & Connell (1989) have demonstrated that different types of behavioural regulation can be located on a continuum of perceived autonomy or perceived locus of causality. The present study applied their formulation in the context of school physical education (PE) and examined the relationships of perceived autonomy, perceived competence and goal orientations with intrinsic interest across two PE activities. School students aged 12-14 years (N = 85) completed an adapted version of the Self-Regulation Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
330
1
90

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(423 citation statements)
references
References 15 publications
2
330
1
90
Order By: Relevance
“…The limitations to our study are: children's performance in cardiorespiratory fitness tests such as the 20mMST may be affected by motivation, 47 although 20mMST remains a reliable indicator of aerobic fitness among school children. 22,23 The number of children participating in the latter years was reduced.…”
Section: Cardiorespiratory Fitness and Bmi Of English Children G Stramentioning
confidence: 95%
See 1 more Smart Citation
“…The limitations to our study are: children's performance in cardiorespiratory fitness tests such as the 20mMST may be affected by motivation, 47 although 20mMST remains a reliable indicator of aerobic fitness among school children. 22,23 The number of children participating in the latter years was reduced.…”
Section: Cardiorespiratory Fitness and Bmi Of English Children G Stramentioning
confidence: 95%
“…The 20mMST scores were higher among boys than girls across all study periods. The 20mMST scores fell in boys from the median number of completed runs of 47 (46)(47)(48)(49) in 1998/9 to 36 (34)(35)(36)(37) There was no significant difference in the secular trend for 20mMST scores between boys and girls. An increasing Cardiorespiratory fitness and BMI of English children G Stratton et al proportion of those in the most unfit category (bottom third of 20mMST) was observed during the 6-year period in boys and girls (Table 2), with almost twofold difference in the proportion of unfit boys observed between 1998/9 and 2003/4.…”
Section: Methodsmentioning
confidence: 99%
“…The elements that make up these climates are: the way the reward systems are used, the way the practice sessions are designed, the way the subjects are grouped, and the way the authority figures evaluate performance. These motivational climates communicate certain objectives and have an influence on the tendency of the students to adopt one motivational goal or the other.In the context of PE, some studies have demonstrated that the motivational climates that promote the orientation toward mastery in PE classes favored more adaptive motivational models in the students, while the climates oriented toward competitiveness promoted less adaptive motivational models (25,39,50). In a review carried out by Ntoumanis and Biddle (35) on the influence of the motivational climate created in PE class and its impact on motivation to do exercise, the authors conclude after reviewing 14 studies that a climate of mastery is related to more adaptive motivational models than is a motivational climate oriented toward competition.…”
mentioning
confidence: 99%
“…21,23 La motivación se evaluó con la escala de Percepción del Locus de Causalidad. 24 Está compuesta por 20 ítems, cuatro para cada subescala: motivación intrínseca, regulación identificada, regulación introyectada, regulación externa, y no motivación. La escala está precedida de la frase: "Participo en esta clase de educación física…".…”
Section: Instrumentosunclassified